Marine medaka heat shock protein 90ab1 is a receptor for red-spotted grouper nervous necrosis virus and promotes virus internalization through clathrin-mediated endocytosis. - Wanwan Zhang; Kuntong Jia; Peng Jia; Yangxi Xiang; Xiaobing Lu; Wei Liu; Meisheng Yi (PLoS Pathogens)
Nervous necrosis virus (NNV) can infect many species of fish and causes serious acute or persistent infection. However, its pathogenic mechanism is still far from clear. Specific cellular surface receptors are crucial determinants of the species tropism of a virus and its pathogenesis. Here, the heat shock protein 90ab1 of marine model fish species marine medaka (MmHSP90ab1) was identified as a novel receptor of red-spotted grouper NNV (RGNNV). MmHSP90ab1 interacted directly with RGNNV capsid protein (CP). Specifically, MmHSP90ab1 bound to the linker region (LR) of CP through its NM domain. Inhibition of MmHSP90ab1 by HSP90-specific inhibitors or MmHSP90ab1 siRNA caused significant inhibition of viral binding and entry, whereas its overexpression led to the opposite effect. The binding of RGNNV to cultured marine medaka hMMES1 cells was inhibited by blocking cell surface-localized MmHSP90ab1 with anti-HSP90β antibodies or pretreating virus with recombinant MmHSP90ab1 or MmHSP90ab1-NM protein, indicating MmHSP90ab1 was an attachment receptor for RGNNV. Furthermore, we found that MmHSP90ab1 formed a complex with CP and marine medaka heat shock cognate 70, a known NNV receptor. Exogenous expression of MmHSP90ab1 independently facilitated the internalization of RGNNV into RGNNV impenetrable cells (HEK293T), which was blocked by chlorpromazine, an inhibitor of clathrin-dependent endocytosis. Further study revealed that MmHSP90ab1 interacted with the marine medaka clathrin heavy chain. Collectively, these data suggest that MmHSP90ab1 is a functional part of the RGNNV receptor complex and involved in the internalization of RGNNV via the clathrin endocytosis pathway.